Fraction Understanding in Children: Bibliometric Analysis - Zahra, Novina Sabila; Susanto, Nadila Apriola; Anugrahastuti, Bernadeta Yosefani; Sabrina, Nur Amalina Naada; Wimbarti, Supra (Buletin Psikologi, 2025)
This study used a bibliometric analysis approach to investigate the literature on children’s development of fraction understanding. Fraction understanding is crucial in early mathematics education because it is the foundation for more advanced concepts. Bibliometric analysis gives a comprehensive data-driven assessment of research trends, significant contributors, and emerging themes in this field. The data were sourced from the Scopus journal database, encompassing 228 articles from 1975 to 2023. Analytical and visualization tools, including VOS Viewer and the Bibliometrix R-Package, were utilized to map connections among journals, authors, countries/regions, and keywords. The findings indicated a trend of increasing publication volume over the past 15 years, with a yearly growth in articles on this topic. Keyword analysis revealed that, within these publications, “fraction” was the most frequently encountered term, followed by “mathematics” and “decimals”. Moreover, there has been a shift in research focus from studying the challenges in conceptual understanding of fractions among children to investigating alternative interventions designed to address these challenges. This study is a foundational reference for future research on the progression of fraction understanding in children.